Ratite cancellous xenograft: effects on avian fracture healing - Mathews, K. G.; Danova, A.; Newman, H.; Barnes, H. J.; Phillips, L. (Veterinary and Comparative Orthopaedics and Traumatology, 2003)
A segmental radial defect model was used to radiographically and histologically evaluate response to ratite cancellous xenograft in pigeons. The control group showed little evidence of callus production with all fractures proceeding to nonunion. Lymphocytic response to xenograft peaked at four weeks and diminished thereafter. Fractures treated with cancellous xenograft had significant increases in new bone production.
Keywords: Avian; bone graft; ratite; cancellous; xenograft